TYPES OF RISKS THAT ARISE DURING THE TRANSPORTATION OF DANGEROUS GOODS IN RAILWAY TRANSPORT - Professor Sh. X. Abdazimov; Professor M. N. Umarova; Asistent J . M. Mirhamitov (International Journal of Innovations in Engineering Research and Technology, 2023)
This article discusses the issue of protection systems against natural and man-made emergencies,informing and notifying employees in railway transport. The issueof risks in railway transport during the transportation of dangerous goods in railway transport through mountainous and near-mountainous areas is considered. . Methods of their prevention.